Conference Review: The Later Prehistoric Finds Group Conference Crafting Identities: Making and Using Objects in the Bronze and Iron Ages - E. Giovanna Fregni (EXARC, 2020)
The one-day conference was held on Saturday 26th October 2019 in Edinburgh at the National Museum of Scotland. The focus was on the importance of understanding craft processes as a means of interpreting the expression of identity in prehistory. This was explored in papers that focussed on crafts and craftworkers who worked in metals, wood, glass, and ceramic materials. The conference began with the question of how identity is interpreted and whether individuality is a modern gloss on personal identity. The presentations discussed how people in prehistory used both local styles and ones that were manufactured in a wider region. These exhibited a continuity in shape, but also creativity in decoration that exhibited improvisation within established tradition. Rather than rely on strict typologies, the emphasis was to examine the process of creation in order to understand individual creative processes.